Hubungan Tingkat Stres dengan Keteraturan Siklus Menstruasi pada Remaja - Larasati, Nabilla Alya (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The menstrual cycle is a complex series of events that influence each other and occur simultaneously. The menstrual cycle can be affected by stress factors. Stress is a perception of threat or of an image of displeasure that moves, alerts or activates the organism. The World Health Organization (WHO) in 2015 stated that the problems of youth in the world are around problems regarding menstrual disorders (38.45%). Menstrual disorders that are not treated can affect the quality of life and daily activities. Menstrual irregularity affects 2-5% of women of childbearing age, a much higher number among women who are under constant stress during their cycles. Objective is to study the effect of perceived stress on cycle length, regularity and dysmenorrhea. This type of research is literature review, using one database, namely pubmed. The keywords used are stress, teenage, menstrual. After being selected, eight literatures were obtained consisting of a cross-sectional method by filling out a questionnaire.